Evaluation of pyrolyzed oil palm frond in the adsorption of residual phenolic compounds in facultatively treated palm oil mill effluent - Lawal, A. A.; Dzivama, A. U.; Aviara, N. A.; Hassan, M. A.; Zakaria, M. R.; Shirai, Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Aerobic digestion is the final stage of biological treatment systems employed for treating Palm Oil Mill Effluent (POME). The presence of phenolic compounds in POME inhibits the performance of aerobic microbes. To mitigate the inhibitory effect, removing phenolic compounds at the early stage of aerobic treatment could be a workable solution. In this study, the performance of biochar from oil palm frond (OPF-BC) prepared using steam pyrolysis was investigated for the efficient removal of phenolic compounds. Adsorption kinetics and equilibrium tests were performed to assess the time required to reach adsorption equilibrium and uptake capacity for phenol, catechol and gallic acid spiked in water and facultatively treated POME. Adsorption of the phenols onto OPF-BC attained equilibrium within 2 h irrespective of the water matrix. In the water maximum adsorption capacities of 38.7, 28.2 and 26.2 mg/g were obtained for phenol, catechol, and gallic acid, respectively. The presence of background organic matter in facultatively treated POME reduced the adsorption capacities by 3-folds. The simplified equivalent background model estimated dosage to achieve 80% removal ranged between 14.4 and 18.8 g/L. The OPF-BC demonstrated efficient phenolic compounds removal performance, making it a promising and economical adsorbent for the hybrid adsorption-aerobic treatment system.